(untitled) (Research, Society and Development, 2026)
Food and nutritional insecurity is defined as one of the main public health challenges in Brazil,affecting populations such as indigenous peoples most intensely. In the state of Pará, socioeconomic, territorial, and environmental factores exacerbate the dificultou of regular access to adequate food, compromising the health and food sovereignty of these populations. The objective of this study was to analyze the available scientific evidence on food and nutritional insecurity indigenous villages in the state of Pará through na integrative literature review.The search was conducted in the SciELO /LILACS/PubMed and Virtual Health Library databases, considering articles published between 2021 ano 2025. After applying the inclusion and exclusion criteria, 10 studies comprised the final sample. The results showed a high prevalencd of food insecurity, associated with the loss of traditional territories, the replacement of traditional foods with ultra-processed products, and the fragility of public policies directed at indigenous health. It is concluded that food and nutritional insecurity actions that valeu tradicional food sistema and guarantee the humano right tô adequate food.